Simulation of Friction Stir Welding Process Temperature Distribution on AA6061-T6 Material Static Position: Simulasi Distribusi Suhu Proses Friction Stir Welding pada Material AA6061-T6 Posisi Statis - Budi, Aan Setia; Mulyadi, Mulyadi (Indonesian Journal of Innovation Studies, 2021)
Friction Stir Welding (FSW) is a welding method that utilizes heat from friction between two objects, namely the tool and the material being welded. To melt the material with heat required about 80% of the melting temperature of the material. In the FSW simulation to predict the temperature distribution on the AA6061-T6 plate measuring 200mm long, 100mm wide, 6mm thick using various pin shapes, namely, cylinder, taper cylinder, hexagonal, and taper square showing at a distance of 140mm with a hexagonal pin the temperature value is 481° C where the temperature is higher than the other pins when measured from the same distance. When using a taper square pin a distance of 190mm the temperature value is 468°C which is the lowest temperature when compared to using other pins when measured from the same distance. The results of the calculation of the heat transfer rate show that the largest energy is 7110 watts which is located at position 1 and close to the FSW tool area. Energy will decrease further if the measured position is further away from the FSW tool position.